Progression of functional and structural glaucomatous damage in relation to diurnal and nocturnal dips in mean arterial pressure - Melgarejo, Jesus D.; Van Eijgen, Jan; Wei, Dongmei; Maestre, Gladys E.; Al-Aswad, Lama A.; Liao, Chia-Te; Mena, Luis J.; Vanassche, Thomas; Janssens, Stefan; Verhamme, Peter; Van Keer, Karel; Stalmans, Ingeborg; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Systemic hypoperfusion plays a pivotal role in the pathogenesis of primary open-angle glaucoma (POAG). Extreme dips in mean arterial pressure (MAP) due to high 24-h variability are associated with POAG, however, whether this is driven by diurnal or nocturnal dips remains undocumented. We aimed this study to investigate the association of POAG damage with variability and dips in the diurnal and nocturnal MAP. Methods We conducted a retrospective longitudinal study that included 110 POAG patients who underwent 24-h ambulatory blood pressure monitoring. Our outcomes included (i) functional [visual field defects expressed as mean deviation (MD)] and (ii) structural (optic disc cupping obtained from cup-to-disc ratio) glaucoma damage. MAP variability independent of the mean (VIMmap) was computed for diurnal and nocturnal MAP. Dips were the five diurnal and three nocturnal lowest drops in MAP. We also calculated the night-to-day ratio. We applied mixed models to evaluate the progression of visual field defects and optic disc cupping in relation to diurnal and nocturnal MAP measures. Results The mean age was 64.0 y (53% women). The median follow-up was 9 years. In adjusted mixed models, functional progression of glaucoma damage was associated with VIMmap (−2.57 dB change in MD per every 3 mmHg increase in VIMmap; P < 0.001) and diurnal MAP dips (changes in the MD ranged from −2.56 to −3.19 dB; P < 0.001). Every 5 mmHg decrease in the nocturnal MAP level was associated with −1.14 dB changes in MD [95% confidence interval (CI), −1.90 to −0.40] and 0.01 larger optic disc cupping (95% CI, 0.01–0.02). Lower night-to-day ratio was also related to both outcomes (P ≤ 0.012). Functional glaucoma damage worsened if nocturnal hypotension was combined with high variability or extreme dips in the diurnal MAP (P ≤ 0.022). Conclusion Progression of glaucoma damage in POAG associates with high variability and extreme dips in the diurnal MAP. Structural glaucoma damage seems more vulnerable to nocturnal hypotension. Ambulatory blood pressure monitoring allows the assessment of sporadic diurnal and persistent nocturnal hypotension episodes. These phenotypes might offer an opportunity to improve the risk-stratification of open-angle glaucoma (OAG).